2018
DOI: 10.1111/jgs.15417
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning for Older Homeless‐Experienced Adults: Results from the Health Outcomes of People Experiencing Homelessness in Older Middle Age Study

Abstract: Older homeless-experienced adults have low engagement in advance care planning (ACP) despite high morbidity and mortality. We conducted a cross-sectional analysis of a cohort of 350 homeless-experienced adults aged 50 and older in Oakland, California. We assessed the prevalence of potential surrogate decision-makers, ACP contemplation, discussions, and ACP documentation (surrogate designation, advance directives). We used multivariable logistic regression to examine factors associated with ACP discussions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…The barriers, including lack of knowledge, social isolation and mistrust, competing demands and lack of training in ACP among staff within and outside the clinic setting provide context to the low prevalence of completion of ACP among the growing population of homeless-experienced older adults. 4 The participants suggested strategies to overcome these barriers, including: reframing the discussion away from death to promote empowerment, moving the ACP discussions out of the clinic visit, capitalizing on the period after housing, and using easy-to-read ACP materials tailored to the specific needs of homeless populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The barriers, including lack of knowledge, social isolation and mistrust, competing demands and lack of training in ACP among staff within and outside the clinic setting provide context to the low prevalence of completion of ACP among the growing population of homeless-experienced older adults. 4 The participants suggested strategies to overcome these barriers, including: reframing the discussion away from death to promote empowerment, moving the ACP discussions out of the clinic visit, capitalizing on the period after housing, and using easy-to-read ACP materials tailored to the specific needs of homeless populations.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, in a prior study in older homeless-experienced adults, we found that 61% reported having a potential surrogate. 4 Professionals working with homeless-experienced older adults should not assume that individuals do not have surrogates but should acknowledge that to initiate ACP, it is not required to have a surrogate or to reach out to family, if the participant chooses to not do so.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study noted that effective ACP was contingent on psychosocial support but further research is needed to understand inmates’ unique psychosocial needs during ACP. Future research should also explore whether knowledge of historical instances of unethical treatment of prisoners could affect decision‐making and the extent to which provider distrust, a barrier to ACP found in ethnic minorities and homeless people, is a challenge in prisons and jails. Because participants identified the need to address policies that limit ACP, the development of a guide that describes exemplary correctional ACP policies could benefit all systems.…”
Section: Discussionmentioning
confidence: 99%